An interactive course program on nutrition for medical students: interdisciplinary development and mixed-methods evaluation - Gonza B. Ngoumou; Daniela A. Koppold; Laetitia Wenzel; Anne Schirmaier; Carolin Breinlinger; Lisa M. Pörtner; Stefan Jordan; Julia K. Schiele; Etienne Hanslian; Annika Koppold; Beate Stock-Schröer; Dimitra M. Varvarezou; et al. (BMC Medical Education)
Abstract Nutrition plays a crucial role in human and planetary health, as prevailing nutritional patterns significantly contribute to the global non-communicable disease pandemic. Moreover, the global food system is inextricably linked to planetary health deterioration. The relevance of nutrition for individual and planetary health is insufficiently addressed in German medical schools. Here, we present a two-week course for medical students in the 8th semester at Charité - Universitätsmedizin Berlin on nutrition and fasting in the context of human and planetary health. The course was developed iteratively along the Kern cycle for medical curricula and underwent evaluation through a mixed-methods design spanning across two consecutive semesters. Assessment involved quantitative questionnaires and qualitative interviews. The main exploratory outcome was the overall module rating. Further outcomes encompassed in-depth evaluations of specific aspects, including content, teaching methods, instructor performance, and subjective experiential aspects. The conceptualisation resulted in a highly participative two-week course of 37.5 h. The main learning objectives aimed at the acquisition of technical competences and personal competencies in four areas: (1) the role of nutrition in health and disease; (2) the exploration of global food systems; (3) communication on subjects of nutrition; (4) culinary medicine. Various interactive didactic methodologies were used. 77.8% (n = 27) of the participants rated the course as very good or good. The conviction that nutrition influences health and disease increased over the course (Wilcoxon signed rank test, z = -2.82, p = 0.005, r = 0.57). In the qualitative interviews (n = 8) the course content, its didactical diversity and the positive group experience were appreciated. Our results indicate that it could be worthwhile to further incorporate nutrition curricula in medical education.